IMPLEMENTASI FUNGSI BADAN PERMUSYAWARATAN KAMPUNG DI KAMPUNG KANDIS KECAMATAN KANDIS KABUPATEN SIAK TAHUN 2015-2016 - Popy Gusti Rahayu; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Local regulation of siak districts policy number 5 year 2015 about Vilage‟s forum institution, in article 3 explain the function of Vilage‟s forum institution is: 1. To Discuss and agree vilage draft regulations with headman.2. Accomodate and channel the vilager aspirations 3. Perform performance monitoring the headman based on Local regulation. The three functions of vilage regulation are expected to be realized well, considering the Village Consultative Agency as a vehicle for democracy within the village. But in the implementation still many the point cannt be realized and there are still many obstacles in the implementation.The purpose of this research is to know how the Implementation of function kandis Vilage‟s forum institution, and want to know what are the constraints that cause the implementation of vilage regulation function difficult to be realizedThe method in this research is qualitative descriptive, by using purposive sampling technique, there are 2 key informant that is headman and Chairman of Vilage‟s forum institutionThe results of this research is to shows that the implementation of Vilage‟s forum institutionfunction has not run maximally, this is indicated by the number of Village regulations be taken out is not balanced with the existing problems in the village. Obstacles found consist of: 1. Educational factors 2. Funding factors 3. Communication factors between chairman and Vilage‟s forum institutionKeywords :Iimplementation, Vilage‟s forum institution, Village Government